REHABILITATION NURSE INTERVENTION IN POSTURAL BALANCE GAIN IN PERSON AFTER STROKE: CASE STUDY - Inês De Jesus Rocha; Maria Félix Martin Bravo; Luís Manuel Mota Sousa; Ana Cristina Nunes Mesquita; Helena Castelão Figueira Carlos Pestana (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Background: A person with stroke may have a loss of control of trunk mobility, which may lead to impaired balance and body posture and, consequently, impaired motor skills for gait recovery and recovery of functional independence. Objective: To identify sensitive gains in rehabilitation nursing care with a program of activities and therapeutic exercises in the recovery of postural balance in stroke patients. Method: Qualitative approach study, case study type. We present the case of an elderly person with altered balance, admitted to the neurology department. The ethical principles in research have been fulfilled. Results: Gains in muscle strength, postural balance and functionality were evidenced after 10 sessions of therapeutic exercises and balance training. Conclusions: The systematization of rehabilitation nursing care has been shown to improve body balance recovery in people with ischemic stroke, maximizing its functionality.